Сушка плотного слоя зерновых материалов (на примере гречихи) при 12 микроволновом нагреве - Волгушева, Наталья Викторовна (НТУ "ХПИ", 2015)
Приведены результаты изучения кинетики сушки зернового материала при микроволновом нагреве. Установлены основные закономерности изменения температуры, влагосодержания, определено условие равномерности микроволновой сушки. Для оценки равномерности процесса сушки сравнивались значения влагосодержаний и температур по радиусу и толщине слоя. Получено, что при влагоизоляции нижней поверхности в процессе сушки увлажняется нижний слой, причем его влагосодержание может становиться выше начального. Предложены гипотезы, объясняющие физический механизм поступления влаги в нижний слой.

The method of microwave drying is of interest as a basis for development new energy saving technologies, as well as the method using which the significant intensification of the process of moisture removal from a material is possible. However, for creation of the industrial equipment it is also necessary to estimate conditions under which drying will be performed in regular intervals by volume. In the article the results of the drying kinetics study have been presented. In the research the changes in the moisture content and the temperature of buckwheat grain by the depth and the radius of the layer in the course of time were studied. It was found that in the course of microwave drying the considerable irregularity both in a radial direction and by depth was possible. Experiments showed, that moisture content of bottom layer increased.
Drying of dense layer of com materials (on example of buckweat) under microwave 12 heating
Keywords: влагосодержание; температура; термодиффузия; гречка; moisture content; temperature; thermodiffusion